2016
DOI: 10.18006/2016.4(issue6).644.652
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality of maize in response to drought stress during grain-filling stages in mediterranean climate condition

Abstract: Maize is considered one of the most essential dietary components in human food and animal feeding. The objectives of the present study were to quantify the effects of drought stress on qualitative traits of maize at grain-filling stages. Hybrids maize seeds were grown by applying full and water stress conditions during the grain filling stage. Various nutritional properties (crude oil, starch, grain protein content) were determined in 2014 and 2015 at the second crop growing season in Adana, Turkey. Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 20 publications
5
19
1
Order By: Relevance
“…We observed that the grain starch concentration was not affected (only reduced by 1.8% and 2.2% at maturity in 2014 and 2015, respectively), but the starch accumulation was severely depressed (reduction was 33.5% and 20.0% at maturity in 2014 and 2015, respectively) by post-silking water deficit, and the severe reduction of starch accumulation in 2014 may be due to the severe reduction of grain dry weight (32.3% and 18.3% in 2014 and 2015, respectively). Similar starch concentration between control and drought stress was observed on fresh waxy maize 21 and normal maize 27 . A field study on normal maize 28 and sorghum 29 also observed that starch content was slightly affected by restrict irrigation.…”
Section: Discussionsupporting
confidence: 75%
“…We observed that the grain starch concentration was not affected (only reduced by 1.8% and 2.2% at maturity in 2014 and 2015, respectively), but the starch accumulation was severely depressed (reduction was 33.5% and 20.0% at maturity in 2014 and 2015, respectively) by post-silking water deficit, and the severe reduction of starch accumulation in 2014 may be due to the severe reduction of grain dry weight (32.3% and 18.3% in 2014 and 2015, respectively). Similar starch concentration between control and drought stress was observed on fresh waxy maize 21 and normal maize 27 . A field study on normal maize 28 and sorghum 29 also observed that starch content was slightly affected by restrict irrigation.…”
Section: Discussionsupporting
confidence: 75%
“…Zhang et al [18] indicated that irrigation deficit during maturation is more damaging than deficit during late vegetative stages due to the limitation of kernel development. In addition, drought significantly reduces starch, protein [19], and mineral contents in maize [9], while Balla et al [20] found a reduction in grain starch and an increase in protein content in maize in response to drought stress.…”
Section: Introductionmentioning
confidence: 94%
“…Stress tolerance indictors are beneficial tools to determine high yield and stress tolerance potential of genotypes of crops [38]. Identifying high-yield genotypes under stress and non-stress conditions are more useful than developing new varieties [19,39]. Due to the continuous increase in irrigation water and global warming, maize production will face big difficulties and, as a result, testing techniques that can enhance drought tolerance in maize have become important.…”
Section: Introductionmentioning
confidence: 99%
“…Herbicide applications, especially the post‐emergence treatment, contributed to maize growth by increasing chlorophyll content in the leaves, whereas N form and row spacing did not influence chlorophyll content. The protein content in maize grains was higher in 2015 and 2016 (9.07 and 9.09%, respectively) than in 2014 (7.85%) because stress conditions increase its content in grain (Barutçular et al., 2016; Wang & Frei, 2011). The protein content was influenced by N form, whereas herbicide treatment and row spacing did not produce any significant differences.…”
Section: Resultsmentioning
confidence: 99%